2021
DOI: 10.1002/jgh3.12679
|View full text |Cite
|
Sign up to set email alerts
|

Longer‐term outcome of acute pancreatitis: 5 years follow‐up

Abstract: Background and Aim Following an index episode of acute pancreatitis, sometimes the inflammation subsides completely, but sometimes inflammation persists and progresses to chronic pancreatitis, which may be or may not be preceded by recurrent acute pancreatitis. Some patients may also develop diabetes mellitus. There is only limited information on the longer‐term outcome of patients with acute pancreatitis. The aim of this study was to evaluate the longer‐term consequences of acute pancreatitis in the form of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…After reviewing the full text of the remaining 66 articles, 24 more articles were excluded (22 articles included patients who had more than one previous episodes of pancreatitis; two studies included the same population as one of the eligible studies). Consequently, 42 studies 8,9,14–53 (32 retrospective cohort, 8 prospective cohort, and 2 randomized controlled trials) including a total of 57 815 patients were eligible for inclusion. The study flow chart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the full text of the remaining 66 articles, 24 more articles were excluded (22 articles included patients who had more than one previous episodes of pancreatitis; two studies included the same population as one of the eligible studies). Consequently, 42 studies 8,9,14–53 (32 retrospective cohort, 8 prospective cohort, and 2 randomized controlled trials) including a total of 57 815 patients were eligible for inclusion. The study flow chart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…We found a significantly greater odds of developing PD/DM with necrotizing AP [OR: 5.53; CI: 1.59–19.21; ( 22 , 31 , 46–48 )] and a statistically non-significant tendency with DM [OR: 3.09; CI: 0.98–9.72; ( 24 , 30 , 36 , 40 , 41 , 49 , 50 )] compared to non-necrotizing AP ( Figure 4 ). Sensitivity analysis revealed that leaving out Takeyama ( 24 ) from the analysis would lead to a statistically significant OR (4.17; CI: 2.08–8.37) of developing DM in AP patients who had necrosis compared to its absence ( Supplementary Figure S28 ).…”
Section: Resultsmentioning
confidence: 95%
“…Similarly, only a statistically non-significant tendency could be observed in case of any organ failure (regardless of organ and duration of impairment) and DM [OR: 3.19; CI: 0.55–18.64; ( 36 , 40 , 45 , 52 )] or PD/DM [OR: 2.14; CI: 0.51–9.06; ( 31 , 32 , 46 ); Figure 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alcoholism, gallstones, pancreatic duct obstruction and gene mutation are the main factors leading to AP [3,4] . Current treatment interventions have largely improved the outcome of AP patients, but the long‐term survival of patients with AP remains a concern [5] . Therefore, it is necessary to further clarify the pathogenesis and development of AP.…”
Section: Introductionmentioning
confidence: 99%